Effect of bank’s sizes and age on the financial performance of deposit money banks in Nigeria - Abass Adekunle Adewale; Saheed Akande Shittu; Joseph Adeyinka Adewole (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
This research explores the impact of bank size and age on the financial performance of deposit money banks in Nigeria. DMB are crucial for allocating funds from savers to investors and managing financial risks. The study aims to determine how bank size and age influence ROA and ROE. Data analysis is conducted using ex post facto research design and panel data analysis. The study reveals a significant strong relationship between bank size and age with ROA and ROE for Nigerian deposit money banks during the period from 2015 to 2021. Increased bank size and age are associated with improved financial performance. The research concludes that bank size and age have a significant impact on the performance of deposit money banks in Nigeria during the specified period. Thus, the study recommends that listed deposit money banks should consider expanding their firm size through strategic expansion initiatives to enhance financial performance. Further research should encompass a broader selection of listed firms in Nigeria and employ diverse analytical tools to validate and expand upon these findings.